ANALISIS ASPEK KELEMBAGAAN PADA KEMITRAAN PETANI CABAI DI KABUPATEN LAMPUNG SELATAN - Yanfika, Helvi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2013)
The success of the partnership program is determined by the compliance between the two parties that are partners in running the partnership business ethics. The partnership is an institution that can not be separated from the functional and structural aspects, so the partnership that exists includes a set of rules, treaties, and agreements are implemented and must be adhered to by each party. The partnership established between the two parties different scale, it is possible that the problem occurs because each party will maximize satisfaction. So far as is known, many partnerships that are not running anymore because of connections made between partner companies and partner farmers do not meet the rights and obligations that have been agreed. Need for clear rules, in this case the rights and obligations of each party to be clear and wellexecuted, which is expected to minimize the occurrence of conflicts in partnership. It is important to know the extent of the institutional aspects of the cultivation and marketing partnership, the terms of aspects of jurisdiction boundaries, rights and obligations of aspects, and aspects of the representation rule. This study aims to analyze the institutional aspects of the partnership between PT Agro Mitratani Unggul with chili farmers, this study was conducted in June-December 2012 with a number of respondents 12 farmers who partner. The analysis showed that the institutional implementation of boundary jurisdiction, rights and obligations, as well as the implementation of the rules of both parties have not done well.